The role of organizational structure and deviant status in employees’ reactions to and acceptance of workplace deviance - Moon, Chanki (2020)
Purpose–This study aims to examine the role of deviant status (lower vs higher rank) and organizational structure (vertical vs horizontal) on individuals’ responses to workplace deviance. Design/methodology/approach–Two studies (N= 472) were designed to examine the role of deviant status and organizational structure in responses to workplace deviance. Study 1 (N= 272) manipulated deviant status and organizational structure. Study 2 (N= 200) also manipulated deviant status but focused on participants’ subjective evaluations of the organizational structure of their workplace. Findings–Study 1 found that participants reported lower job satisfaction and organizational commitment, and higher turnover intentions when they imagined being confronted with deviant behaviors displayed by a manager (vs by a subordinate), regardless of the type of organizational structure. Study 2 extended this finding by showing that the indirect effect of organizational structure (vertical vs horizontal) on turnover intention via job satisfaction and organizational commitment was moderated by deviant status: when the deviant’s status was higher, working in a vertical (vs horizontal) organization was associated with decreased job satisfaction and commitment, which, in turn, was associated with a higher level of turnover intentions. Originality/value–The findings broaden our understanding of how individuals respond to deviance at the workplace, by simultaneously considering the effects of organizational structure (vertical vs horizontal) and deviant status (upward vs downward directions of deviance).